Analysis of kinematically redundant reaching movements using the equilibrium-point hypothesis - Cesari, Paola; Shiratori, Takako; Olivato, Paolo; Duarte, Marcos (Biological cybernetics, 2001)
Six subjects performed a planar reaching arm movement to a target while unpredictable perturbations were applied to the endpoint; the perturbations consisted of pulling springs having different stiffness. Two conditions were applied; in the first, subjects had to reach for the target despite the perturbation, in the second condition, the subjects were asked to not correct the motion as a perturbation was applied. We analyzed the kinematics profiles of the three arm segments and, by means of inverse dynamics, calculated the joint torques. The framework of the equilibrium-point (EP) hypothesis, the lambda model, allowed the reconstruction of the control variables, the "equilibrium trajectories", in the "do not correct" condition for the wrist and the elbow joints as well as for the end point final position, while for the other condition, the reconstruction was less reliable. The findings support and extend to a multiple-joint planar movement, the paradigm of the EP hypothesis along with the "do not correct" instruction.